Конституційно-правові засади забезпечення юридичної відповідальності держави в сучасній Україні в умовах дії особливих правових режимів - Бакумов, О. С.; Bakumov, O. S.; ORCID: https://orcid.org/0000-0002-4003-1974 (Юридична наука. - 2019. - № 5 (95). - С. 169-182, 2019)
Встановлено конституційно-правові особливості забезпечення юридичної відповідальності держави в сучасній Україні в умовах дії особливих правових режимів. Правове регулювання юридичної відповідальності держави у межах Конституції України та спеціальних законів, що обумовлюють запровадження та дію відповідних правових режимів, не відзначається завершеним та системним характером, що пояснюється як різним часом ухвалення відповідних актів, так і концептуальною неопрацьованістю питань покладення юридичної відповідальності на державу в умовах особливого правового режиму. Природно, що залежно від специфіки того чи іншого особливого правового режиму юридична відповідальність держави має бути істотно специфікована.

The article investigates the constitutional and legal features of ensuring the legal responsibility of the state in modern Ukraine in the context of the special legal regimes. It is emphasized that a special legal regime should be understood as a special procedure for ensuring the rights and freedoms of Ukrainian citizens living in the territories within which appropriate legal regimes, limited in space, time and in terms of persons, are introduced, and also provide for substantial legal restrictions, which entail significant changes in the organization and functioning of the system of public authorities, different from the ordinary conditions stipulated by the Constitution and laws of Ukraine. These legal regimes include emergencies (state of emergency, martial law, environmental emergency) and hybrid regimes (antiterrorist operation, joint operations, regime established in the Chernobyl exclusion zone). The main difference between them is expressed in the constitutionalization of the former (which imply the state's retreat from the provision of a number of constitutional rights and freedoms of man) and much less restriction of people in rights, due to extraordinary circumstances not provided for in the Basic Law of Ukraine. It is concluded that the legal responsibility of the state in the conditions of normal and special legal regime cannot be identical, since under the conditions of special legal regime there is a significant restriction of the rights of a certain circle of individuals and legal entities, it is modified as a system of state power, conditions of their functioning, and nature of relations. with individuals and legal entities as a result of increasing the number of restrictions and prohibitions on the life of the latter. Legal regulation of the legal responsibility of the state within the framework of the Constitution of Ukraine and special laws that stipulate the introduction and operation of the respective legal regimes is not marked by a complete and systematic nature, which is explained both by the different time of adoption of the relevant acts and the conceptual failure of the issues of imposing legal responsibility on the state. special legal regime. Naturally, depending on the specifics of a particular legal regime, the legal responsibility of the state should be substantially specified.

Определены конституционно-правовые особенности обеспечения юридической ответственности в современной Украине в условиях действия особых правовых режимов. Отмечается, что во особыми правовыми режимами следует понимать особые порядки обеспечения прав и свобод граждан Украины, проживающих на территориях, в пределах которых вводятся соответствующие режимы, имеют ограниченный во времени, пространстве и по кругу лиц характер, предусматривают существенные правоограничения по осуществлению прав и свобод человека и гражданина, а также влекут существенные изменения в организации и функционировании системы государственной власти, отличные от обычных (ординарных) условий, установленных Конституцией и законами Украины. Правовое регулирование юридической ответственности в рамках Конституции Украины и специальных законов, обусловливающих внедрение и действие соответствующих правовых режимов, не отмечается завершенным и системным характером, что объясняется как различным временем принятия соответствующих актов, так и концептуальной неразработанностью вопросов возложения юридической ответственности на государство в условиях особого правового режима. Естественно, что в зависимости от специфики того или иного особого правового режима юридическая ответственность государства должна быть существенно специфицированы.
Constitutional and legal bases of ensuring the legal responsibility of the state in modern Ukraine in the conditions of special legal regimes
Конституционно-правовые основы обеспечения юридической ответственности в современной Украине в условиях действия особых правовых режимов
Бакумов, О. С. Конституційно-правові засади забезпечення юридичної відповідальності держави в сучасній Україні в умовах дії особливих правових режимів / О. С. Бакумов // Юридична наука. - 2019. - № 5 (95). - С. 169-182.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; юридична відповідальність; legal responsibility; юридическая ответственность; особливі правові режими; special legal regimes; особые правовые режимы; обмежувальні заходи; restrictive measures; ограничительные меры; конституційно-правові засади; constitutional and legal principles; конституционно-правовые основы; правове регулювання; legal regulation; правовое регулирование